The Development of Arts Culture Learning Media Materials of Simple Musical Instrument Games Using Powtoon Animation in Class VII SMP Negeri 15 Padang - Putri Johana; Ardipal Ardipal (Postgraduate School, Universitas Negeri Padang, 2022)
This study aimed to develop learning media for the arts and culture of simple musical instrument games using valid, practical, and effective powtoon animations. This was motivated by the fact that the art and culture learning material for simple musical instrument games previously used the kinemaster application; the videos made were reasonably straightforward, namely only containing material, basic competencies display, indicators, video back sound (dubbing), and examples of video clips of simple musical instrument games. However, in the video, there were no quizzes and guidelines for playing simple musical instruments. This caused students to become monotonous when following the learning process. Therefore, student learning outcomes were decreased. The type of research was research and development used a 4-D model with the stages of definition, design, development, and dissemination. In this study, the dissemination phase was not carried out because of the limitations of the researchers. At the definition stage, curriculum analysis and student analysis were carried out. At the design stage, learning media design was carried out in video shows, pictures, music illustrations, and guidelines for playing simple musical instruments correctly and adequately. Finally, at the development stage, validity, practicality, and effectiveness tests were conducted. The research data were obtained through a validation questionnaire sheet, a valid questionnaire, and a student observation sheet. The validity test results showed that the learning media for the arts and culture of simple musical instrument games using animation powtoon media were developed very validly. Furthermore, the results of the practicality test show that the learning media for the arts and culture of simple musical instrument games using the animation powtoon media were developed very practical. Therefore, based on the effectiveness results, it was stated that the learning media for the arts and culture of simple musical instrument games using animation powtoon media was effectively used.